Developments in Sustainable Chemical and Bioprocess Technology - Pogaku, Ravindra.; Pogaku, Ravindra.; Bono, Awang.; Bono, Awang.; Chu, Christopher.; Chu, Christopher. (Springer US : Imprint: Springer, 2013)
Developments in Sustainable Chemical and Bioprocess Technology is an emerging, multidisciplinary field with applications to the production of chemicals, fuels, materials, and pharmaceuticals. The field's novelty lies in the integration of the techniques and various diverse technologies with the tools of mathematical analysis. The case studies are elucidated for rational selection of targets for process modifications. By providing a rigorous description of chemical and bioprocesses a sustainable approach is highlighted. Key elements of the book include process integration and consideration of technology as a fundamental determinant of sustainable development. Chemical and bioprocesses mathematical complexity is kept to a minimum and provides sidebars as additional background on various mathematical operations. Computational tools for process analysis are described, and a glossary of biological terms facilitates use of the book by a broad audience of chemists, chemical engineering, biotechnologists, microbiologists, and biochemical/biomedical engineers.